Overview on eating disorders - Zam, Wissam; Saijari, Reham; Sijari, Ziad (Progress in Nutrition, 2018)
There is a commonly held view that eating disorders are lifestyle choice. Eating disorders are actually serious and often fatal illnesses, obsessions with food, body weight, and shape may also signal an eating disorders. Common eating disorders include anorexia nervosa, bulimia nervosa, night-eating syndrome, eating disorders not otherwise specified and binge-eating disorders. Eating disorders occur in men and women, young and old, rich and poor and from all cultural backgrounds; they result in about 7000 death a year as of 2010, making them the mental illnesses with the highest mortality rate. The chance for recovery increases the earlier they are detected, therefore, it is important to be aware of some of the warning signs of an eating disorder. In this review, different types of eating disorder, their side effects, complications and treatments are discussed.